2020
DOI: 10.3390/microorganisms8111671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approach for the Diagnosis of Blood and Skin Canine Filarioids

Abstract: The zoonotic Onchocerca lupi and tick-transmitted filarioids of the genus Cercopithifilaria remain less well known due to the difficulties in accessing to skin samples as target tissues. Here, we proposed a molecular approach reliying on multiplex qPCR assays that allow the rapid identification of filarioids from canine blood, skin, and tick samples. This includes two newly developed duplex qPCR tests, the first one targeting filarial and C. grassii DNA (CanFil-C. grassii). and the second qPCR assay designed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, there are important limitations to consider when interpreting the results from serologic analyses, including the occurrence of false-positive and false-negative results. Molecular approaches have been developed as an alternative and/or complementary diagnostic method for the detection of D. immitis in companion animals ( Laidoudi et al, 2020a , 2020b ). However, the diagnostic potential of molecular tools for the screening of heartworm disease in wild carnivores has not been fully tapped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are important limitations to consider when interpreting the results from serologic analyses, including the occurrence of false-positive and false-negative results. Molecular approaches have been developed as an alternative and/or complementary diagnostic method for the detection of D. immitis in companion animals ( Laidoudi et al, 2020a , 2020b ). However, the diagnostic potential of molecular tools for the screening of heartworm disease in wild carnivores has not been fully tapped.…”
Section: Discussionmentioning
confidence: 99%
“…Even though molecular techniques present some limitation, these methods can provide a rapid, sensitive, and accurate diagnoses, and prevent the occurrence of false-positive results due to cross-reactivity. Several studies have reported the use of molecular approaches targeting conserved DNA regions in the diagnosis of numerous filarial nematodes ( Laidoudi et al, 2020a , 2020b ; Panetta et al, 2021 ; Rishniw et al, 2006 ). As expected, with the present study the real-time PCR technique had a higher positive rate than conventional PCR and seems to be an alternative diagnostic method for detecting D .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the routine use of in-clinic rapid tests for the detection of D. immitis antigens in blood samples has facilitated the diagnosis of this major filarial worm in dogs, but has likely contributed to a reduction in the opportunity to diagnose A. reconditum infections through the Knott's test that is a time-consuming procedure (Magnis et al 2013;Evans et al 2019). Recently, the molecular methods that allow to achieve a diagnosis at species level for A. reconditum have increased compared to testing modalities used in the past (Laidoudi et al 2020a(Laidoudi et al , 2020b, but as they are cannot yet be considered a routine diagnostic resource.…”
Section: Discussionmentioning
confidence: 99%
“…Occult infections with D. immitis can represent about 20-30% of all cases. In this situation, it is recommended to perform a method of detection/identification of microfilariae (Knott) as well as an antigen test [6,10,37,43,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%